2003
DOI: 10.1073/pnas.1133870100
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein 1 in obesity and insulin resistance

Abstract: This study identifies monocyte chemoattractant protein 1 (MCP-1) as an insulin-responsive gene. It also shows that insulin induces substantial expression and secretion of MCP-1 both in vitro in insulin-resistant (IR) 3T3-L1 adipocytes and in vivo in IR obese mice (ob͞ob). Thus, MCP-1 resembles other previously described genes (e.g., PAI-1 and SREBP-1c) that remain sensitive to insulin in IR states. The hyperinsulinemia that frequently accompanies obesity and insulin resistance may therefore contribute to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
761
8
16

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,029 publications
(824 citation statements)
references
References 37 publications
39
761
8
16
Order By: Relevance
“…Recent studies show that expression and secretion of MCP-1 is induced by insulin. 31 This is in line with our observation that insulin administration lead to an elevation of both MCP-1 messenger expression and protein level in GDM patients treated with diet and insulin to the level in normal patients. The significance of the decrease of MCP-1 in GDM patients on dietary monotherapy remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent studies show that expression and secretion of MCP-1 is induced by insulin. 31 This is in line with our observation that insulin administration lead to an elevation of both MCP-1 messenger expression and protein level in GDM patients treated with diet and insulin to the level in normal patients. The significance of the decrease of MCP-1 in GDM patients on dietary monotherapy remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies reported the increase of MCP-1 serum levels in patients with obesity, insulin resistance and Type II diabetes. [31][32][33][34] Surprisingly, GeneCalling showed that MCP-1 mRNA was downregulated in GDM patients on diet therapy compared to normal patients and GDM patient on diet and insulin therapy. We investigated whether this change in gene expression translated to a similar change in serum protein levels for MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…The adipocyte-secreted MCP-1 was recently demonstrated to be induced by IL-6 and TNFα and to decrease insulin-stimulated glucose uptake as well as the expression of GLUT4, aP2 and PPARγ [49]. Furthermore, MCP-1 and other macrophage-related genes were reduced in ob/ob mice following thiazolidinedione treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…11 MCP1 is increased in the circulation of obese subjects, is produced by adipose tissue, and decreases glucose uptake in adipocytes. [12][13][14] Both MCP1 and 5LO products recruit leukocytes to sites of inflammation. 15 These data indirectly suggest that ALOX5AP also might play a role in obesity.…”
Section: Introductionmentioning
confidence: 99%